Biochemical characterization of the malaria parasite Plasmodium falciparum CLpB homologue PfClpB1 localized to the apicoplast - Ngansop, Fabrice (Kansas State University, 2013)
ClpB is a molecular chaperone that is essential for infectivity and pathogen survival in a host. It belongs to the AAA+ protein family, which cooperates with the DnaK chaperone system to reactivate aggregated proteins. In this study, we purified and then studied the biochemical properties of the apicoplast targeted ClpB isoform from the malaria parasite Plasmodium falciparum: PfClpB1. Plasmodium falciparum is the parasite responsible for the most severe form of malaria. In contrast to the parasitophorous vacuole targeted PfClpB2 from Plasmodium falciparum which contains all characteristic AAA+ sequence motifs, PfClpB1 also includes a 52-residue long non-conserved insert in the middle domain. The ATPase activity study shows that PfClpB1 hydrolyzes ATP in presence of Poly-lysine and α-casein. Similar to most AAA+ ATPases, addition of ATP induces hexamer formation in PfClpB1. Lastly, PfClpB1 reactivates aggregated firefly luciferase. However, PfClpB1 is unable to efficiently reactivated luciferase in the presence of the E. coli DnaK chaperone system or human Hsp70 and Hsp40 (Hdj1). This can be explained by the extra middle domain sequence of PfClpB1. Our data may suggest that PfClpB1 activity is essential for Plasmodium falciparum survival by preserving the activity of apicoplast proteins.
Keywords: Plasmodium; Falciparum; Apicoplast; CLPB; MALARIA; PfClpB1; Biochemistry (0487)